Text for Brig. Gen. Dato’ Prof. Dr. Kamarudin Hussin Vice Chancellor Universiti Malaysia Perlis (UniMAP) for an Evening with the Vice Chancellor - Kamarudin, Hussin, Brig. Gen. Dato’ Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event was held at Dewan Kapitol UniMAP Kangar, Perlis.